Three-Dimensional Kinematics of the Pelvis and Caudal Lumbar Spine in German Shepherd Dogs - Schaub, Katharina I.; Kelleners, Nicola; Schmidt, Martin J.; Eley, Nele; Fischer, Martin S. (Frontiers in Veterinary Science, 2021)
Lumbosacral vertebral motion is thought to play a major role in the development of degenerative lumbosacral stenosis in German shepherd dogs. So far, few studies exist describing natural canine lumbosacral movement in vivo. Therefore, this investigation aims to achieve a detailed in vivo analysis of bone movement of the lumbosacral region to gain a better understanding of the origin of degenerative lumbosacral stenosis using three-dimensional non-invasive in vivo analysis of canine pelvic and caudal lumbar motion (at L6 and L7). Biplanar cineradiography of the pelvis and caudal lumbar spine of four clinically sound German shepherd dogs at a walk and at a trot on a treadmill was recorded. Pelvic and intervertebral motion was virtually reconstructed and analyzed with scientific rotoscoping. The use of this technique made possible non-invasive measurement of physiological vertebral motion in dogs with high accuracy. Furthermore, the dogs’ gait patterns revealed a wide variation both between dogs and between individual steps. Pelvic motion showed a common basic pattern throughout the stride cycle. Motion at L6 and L7, except for sagittal rotation at a trot, was largely asynchronous with the stride cycle. Intervertebral motion in all dogs was small with approximately 2–3° rotation and translations of approximately 1–2 mm. The predominant motion of the pelvis was axial rotation at a walk, whereas lateral rotation was predominant at a trot. L7 showed a predominance of sagittal rotation (with up to 5.1° at a trot), whereas lateral rotation was the main component of the movement at L6 (about 2.3° in both gaits). During trotting, a coupling of various motions was detected: axial rotation of L7 and the pelvis was inverse and was coupled with craniocaudal translation of L7. In addition, a certain degree of compensation of abnormal pelvic movements during walking and trotting by the caudal lumbar spine was evident.